Early Miocene Exhumation of High-Pressure Rocks in the Himalaya: A Response to Reduced India-Asia Convergence Velocity - Maiti, Giridas; Mandal, Nibir (Frontiers in Earth Science, 2021)
Low-viscosity channel flow, originating from a melt-weakened mid-crustal layer, is one of the most popular tectonic models to explain the exhumation of deep-seated rocks in the Greater Himalayan Sequence (GHS). The driving mechanism of such channel flow, generally attributed to focused erosion in the mountain front, is still debated, and yet to be resolved. Moreover, the channel flow model cannot explain eclogites in the GHS. In this study, we present a new two-dimensional thermo-mechanical numerical model, based on lubrication dynamics to demonstrate the exhumation process of deep crustal rocks in GHS. The model suggests that a dynamic-pressure drop in the Himalayan wedge, following a large reduction in the India-Asia convergence velocity (15 cm/yr at 50 Ma to nearly 5 cm/yr at ~22 Ma) localized a fully developed extrusion zone, which controlled the pressure-temperature-time (P-T-t) path of GHS rocks. We show that the wedge extrusion, originated in the lower crust (~60 km), was initially bounded by two oppositely directed ductile shear zones: the South Tibetan Detachment systems (STDS) at the top and the Higher Himalayan Discontinuity (HHD) at the bottom. With time the bottom shear boundary of the extrusion zone underwent a southward migration, forming the Main Central Thrust (MCT) at ~17 Ma. Our model successfully reproduces two apparently major paradoxical observations in the Himalaya: syn-convergence extension and inverted metamorphic isograds. Model peak P (10-17 kb) and T (700-820ºC) and the exhumation P-T-t path estimated from several Lagrangian points, travelling through the extrusion zone, are largely compatible with the petrological observations in the GHS. The model results account for the observed asymmetric P-T distribution between the MCT and STDS, showing peak P-T values close to the MCT. The lubrication dynamics proposed in this article sheds light on the fast exhumation event (> 1 cm/yr) in the most active phase of crustal extrusion (22-17 Ma), followed by a slowed-down event. Finally, our model explains why the extrusion zone became weak in the last 8-10 Ma in the history of India-Asia collision.